2005
DOI: 10.1021/bi047383o
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Model for the Osmosensor, Transporter, and Osmoregulator ProP ofEscherichia coli

Abstract: Transporter ProP of Escherichia coli, a member of the major facilitator superfamily (MFS), acts as an osmosensor and an osmoregulator in cells and after purification and reconstitution in proteoliposomes. H(+)-osmoprotectant symport via ProP is activated when medium osmolality is elevated with membrane impermeant osmolytes. The three-dimensional structure of ProP was modeled with the crystal structure of MFS member GlpT as a template. This GlpT structure represents the inward (or cytoplasm)-facing conformation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
95
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(103 citation statements)
references
References 68 publications
8
95
0
Order By: Relevance
“…In the future, this issue will be examined quantitatively, using new tools for substrate binding experiments that could be useful in a wide range of pH conditions. In summary, the results of the kPROT analysis and the successful construction of a 3D model for MdfA strongly support the prediction that MFS transporters generally have a similar fold in the membrane (21)(22)(23)(24)(25). The 3D model of MdfA, as presented here, further substantiates important previous predictions regarding the mechanism underlying Mdr transport.…”
Section: Discussionsupporting
confidence: 85%
“…In the future, this issue will be examined quantitatively, using new tools for substrate binding experiments that could be useful in a wide range of pH conditions. In summary, the results of the kPROT analysis and the successful construction of a 3D model for MdfA strongly support the prediction that MFS transporters generally have a similar fold in the membrane (21)(22)(23)(24)(25). The 3D model of MdfA, as presented here, further substantiates important previous predictions regarding the mechanism underlying Mdr transport.…”
Section: Discussionsupporting
confidence: 85%
“…The osmolality at which ProP activity is half-maximal (⌸ 1/2 /RT) depends on the structure of the transporter (21,27,28,34,48) and the solvent to which it is exposed (42). The positive correlations among growth medium osmolality, the CL content of E. coli, and ⌸ 1/2 /RT for ProP suggested that ⌸ 1/2 /RT is also elevated by a CL-rich membrane environment (7).…”
Section: Subcellular Locations Of CL Lacymentioning
confidence: 99%
“…[11][12][13][14][15]54,55 Nevertheless, significant sequence homology with LacY has been found with only a few bacterial transporters grouped in the Oligosaccharide/H + Symport subfamily. 3 A BLAST search was performed using the translated genomic databases starting from the amino acid sequence of the maltose permease (MaltP) homolog from the deep sea alkalophile B. halodurans ,56 a homolog of LacY with conservation of the most essential amino acid residues (17% identity, see Table 1).…”
Section: Eukaryotic Homologsmentioning
confidence: 99%
“…8,9 As summarized in a recent review, 10 a large amount of biochemical and biophysical data have been obtained for LacY over the last 20 years, much of which is confirmed by the crystal structure. 5 LacY has been used to model tertiary structures of different MFS transporters, [11][12][13][14][15][16] but significant homology of amino acid residues involved in substrate binding and H + translocation is apparent for only a few prokaryotic transporters, [17][18][19][20][21] The availability of a LacY X-ray structure allows homology threading of MFS sugar transporters that have amino acid sequences similar to LacY. The process yields a predicted low resolution structure 22 in which accuracy depends upon the level of homology between proteins, and together with sequence alignment, may provide a powerful tool for predicting amino acid residues that may be mechanistically important.…”
Section: Introductionmentioning
confidence: 99%